1998
DOI: 10.2116/analsci.14.595
|View full text |Cite
|
Sign up to set email alerts
|

Anion Sensing by a Thiourea Based Chromoionophore via Hydrogen Bonding

Abstract: Development of chromogenic receptors for biologically important substrates is one of the current research topics in analytical chemistry and biochemistry. A wide variety of chromoionophores for cations such as alkali and alkaline-earth metal ions 1 as well as amines 2,3 have been reported. In contrast, only a few chromoionophores have been reported for the colorimetric determination of anions in solution. [4][5][6][7] In design and fabrication of new anion receptors for applications in aprotic media [8][9][10]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 19 publications
0
50
0
Order By: Relevance
“…[28] A fluorescent anion sensor based on a pyrene electron acceptor linked to a thiourea donor and a colorimetric sensor based on p-nitrophenylthiourea have been prepared. [29,30] Gunnlaugsson and co-workers have developed similar chemosensors for anions by using anthracene-based fluorescent sensors. [20,31,32] Other examples of recently synthesised thiourea sensors include hosts with the thiourea group linked to fluorescent sensor moieties by a rigid hydrazine spacer selective for acetate, [33][34][35][36] Hosts based on coumarin sensors that act as both fluorescent and colorimetric sensors [37] and compounds that utilise cooperativity between the thiourea group and an amine group adjacent to a naphthalimide sensor are also known.…”
Section: Introductionmentioning
confidence: 99%
“…[28] A fluorescent anion sensor based on a pyrene electron acceptor linked to a thiourea donor and a colorimetric sensor based on p-nitrophenylthiourea have been prepared. [29,30] Gunnlaugsson and co-workers have developed similar chemosensors for anions by using anthracene-based fluorescent sensors. [20,31,32] Other examples of recently synthesised thiourea sensors include hosts with the thiourea group linked to fluorescent sensor moieties by a rigid hydrazine spacer selective for acetate, [33][34][35][36] Hosts based on coumarin sensors that act as both fluorescent and colorimetric sensors [37] and compounds that utilise cooperativity between the thiourea group and an amine group adjacent to a naphthalimide sensor are also known.…”
Section: Introductionmentioning
confidence: 99%
“…For example, high stability constants of (thio)urea derivatives bearing a variety of substituents with hydrophilic anions, such as H2PO4 -, have been previously reported. [51][52][53][54] Their hydrogen-bonding abilities can also afford their use as organic gelators. [46][47][48][49] A phenylurea-modified tip (PhUET-tip) was used to measure the adhesion force on the COOH-terminated SAM (MHA-SAM) surface.…”
Section: Hydrogen Bonding Force Between Phenylurea and Carboxyl Groupmentioning
confidence: 99%
“…Recently, the hydrogenbonding ability of (thio)urea compounds has received considerable attention, and has been utilized to develop highly functionalized novel materials, such as organic gelators, [46][47][48][49] and synthetic receptors for hydrophilic anions, 50 including H2PO4 -, [51][52][53][54] halide, [55][56][57][58][59][60] and ATP. 61 It has been reported that the silica nanosphere catalyst, functionalized with a urea derivative (i.e., ureidopropyl group), can activate the carbonyl compound, a reaction substrate for its catalytic reactions, based on the urea's hydrogen-bonding ability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a variety of these artificial host molecules with specific hydrogenbonding ability have been reported for sensing hydrophilic anions. [1][2][3][7][8][9][10][11][12][13][14] As mentioned above, anion recognition under aqueous conditions, and therefore effective sensing systems of hydrophilic anions, are still challenging to study. This difficulty in anion sensing can be ascribed to the low charge density, geometrical variety, and high hydration energy of anions.…”
Section: Introductionmentioning
confidence: 99%